167k views
0 votes
Whats -3(4x+3)+4(6x+1)=43

2 Answers

5 votes

Step 1. Expand

-12x - 9 + 24x + 4 = 43

Step 2. Simplify -12x - 9 + 24x + 4 to 12x - 5

12x - 5 = 43

Step 3. Add 5 to both sides

12x = 43 + 5

Step 4. Simplify 43 + 5 to 48

12x = 48

Step 5. Divide both sides by 12

x = 48/12

Step 6. Simplify 48/12 to 4

x = 4

User Domchi
by
5.6k points
4 votes


Solution, -3\left(4x+3\right)+4\left(6x+1\right)=43\quad :\quad x=4


Steps:


\mathrm{Expand\:}-3\left(4x+3\right)+4\left(6x+1\right):\quad 12x-5, 12x-5=43


\mathrm{Add\:}5\mathrm{\:to\:both\:sides}, 12x-5+5=43+5


\mathrm{Simplify}, 12x=48


\mathrm{Divide\:both\:sides\:by\:}12, (12x)/(12)=(48)/(12)


\mathrm{Simplify}, x=4

The correct answer is x=4

Hope this helps!!!

<3 -austint1414

User Ramzy Hassan
by
5.3k points